2018
DOI: 10.12741/ebrasilis.v11i3.753
|View full text |Cite
|
Sign up to set email alerts
|

Ataque de Trigona spinipes (Fabr.) (Hymenoptera: Apidae: Meliponinae) em pitaia Hylocereus undatus (Haw.) e Hylocereus polyrhizus (Weber) (Cactaceae) em Couto de Magalhães de Minas, Minas Gerais, Brasil

Abstract: Resumo. A pitaia Hylocereus spp. (Cactaceae) é uma espécie frutífera exótica com cultivo em fase de expansão no Brasil. Problemas com pragas ainda são poucos relatados. Com isso, o objetivo deste trabalho foi relatar a ocorrência da abelha arapuá Trigona spinipes (Fabr.)(Hymenoptera: Apidae) em espécies de pitaia Hylocereus undatus (Haw.) e Hylocereus polyrhizus (Weber) no município de Couto de Magalhães de Minas, Minas Gerais, Brasil. Os danos principais decorrentes do ataque ocorrem nos frutos maduros, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…For example, the study carried out by (BOIÇA JR; SANTOS; PASSILONGO, 2004) investigated the population fluctuation of T. spinipes bees in seven varieties of passion fruit and found that the presence of these insects resulted in a significant decrease in the number of fruits produced. Similar results were observed in the planting of dragon fruit (Hylocereus undatus and Hylocereus polyrhizus) (ALVES et al, 2018). These studies suggest that the role of T. spinipes in pollination may vary according to the specific crop and its interactions with other species.…”
Section: Resultssupporting
confidence: 79%
“…For example, the study carried out by (BOIÇA JR; SANTOS; PASSILONGO, 2004) investigated the population fluctuation of T. spinipes bees in seven varieties of passion fruit and found that the presence of these insects resulted in a significant decrease in the number of fruits produced. Similar results were observed in the planting of dragon fruit (Hylocereus undatus and Hylocereus polyrhizus) (ALVES et al, 2018). These studies suggest that the role of T. spinipes in pollination may vary according to the specific crop and its interactions with other species.…”
Section: Resultssupporting
confidence: 79%
“…T. spinipes jaws cut the tissues of the plants causing a release of certain secretions, resins or brous laments for the construction of their nests in the branches of the trees or, in abandoned termite mounds (Moura et al 2017). In addition to the injuries caused by the direct attack of this insect, such as destruction of ower buds, new branches, owers and fruits (Gallo et al 2002), the exposure of tissues can allow the entry of pathogens, causing even greater problems in production (Alves et al 2018).…”
Section: Qualitative Datamentioning
confidence: 99%